Analisis Location Quotient (LQ) Dalam Menentukan Sektor Unggulan Di Kabupaten Asahan Sumatera Utara - Siregar, Fahmi Apriansyah; Yusuf, Muhammad; Abdi, Muhammad; Aisyah, Shabilla; Anzani, Wandira; Runggu Sihombing; Anggriani, Dwi (Pusat Riset dan Inovasi Nasional, 2025)
The need to identify key industries that can promote economic growth in Asahan Regency, North Sumatra, is the foundation of this study. In order to facilitate more efficient development planning, this study aims to identify top sectors using Location Quotient (LQ) analysis. The Central Statistics Agency (BPS) of Asahan Regency and North Sumatra Province provided the GRDP data at current prices for the 2019–2024 period, and LQ analysis was employed to identify the base and non-base sectors. According to the findings, several industries have a LQ value greater than one, which suggests that they are either the area's base or leading industry. According to the study's findings, LQ analysis is useful for locating possible leading industries, which can assist local governments in creating focused and long-lasting policies for economic development.